(Post)Soviet Russia vs the West: The Ideological Enemy’s Image in English Translations of Fiction - Rudnytska, Nataliya (Vertimo studijos, 2023)
Abstract. The Russo-Ukrainian war, especially the full-scale invasion of 2022, made the issue of manipulation particularly topical, including skewed representation in translation. On the basis of a detailed analysis of linguistic choices of translators, considered within the broad historical-political and ideological context, the paper demonstrates the discrepancies between the images of the (post)Soviet Russian and Western societies created in the novels by the contemporary Russian authors Oleg Pavlov, Viktor Pelevin, Vladimir Sorokin and Lyudmila Ulitskaya and those reproduced in the English translations. The ramifications of such modification acquire special significance under the circumstances, especially due to the increased attention to translation as an “ideological weapon” on the part of the Russian scholars and critics.
Keywords: literary translation; ideology; representation; contemporary Russian literature